FASHIONABLE DEMOCRACY : BANALITAS IKLAN POLITIK DI RUANG PUBLIK - Ali Minanto (LP3 UMY, 2015)
Convergence of political ond economic liberolizotion that swept the 'new democracies' countries makes political events as an industry. Electoral democrocy which makes direct elections as the woy has led democrocy subject to the codes of consumerism. Political advertising, as a form of political communication was packaged as commodities that rely on images. Political rite and democracy agendo oligned uniformly refer to Americon style (Americanized) that uses imagery. ln a way, democrocy has lost its orientation towards the ideal of creating equality ond freedom. Democracy which is tropped as a procedurol mechanical activity without value and only a trend is devoid of the ideals of chonge and politicol moturotion.